2009
DOI: 10.1128/aem.02641-08
|View full text |Cite
|
Sign up to set email alerts
|

Isolation from Sewage Influent and Characterization of Novel Staphylococcus aureus Bacteriophages with Wide Host Ranges and Potent Lytic Capabilities

Abstract: Staphylococcus aureus is a gram-positive pathogen that causes a variety of diseases, including bovine mastitis, which has severe economic consequences. Standard antibiotic treatment results in selection of resistant strains, leading to a need for alternative treatments, such as bacteriophage therapy. Forty-nine S. aureus isolates were obtained from the milk of mastitic cows for use in screening of staphylococcal phages. Fifteen isolates which were positive for both coagulase and hemolysin were assayed by PCR f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
139
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 28 publications
5
139
0
2
Order By: Relevance
“…However the development of resistant bacteria environmentally isolated Enterobacter cloacae (accession no: KF975427) strain were isolated and characterized. The TSE phages were isolated from sewage exhaust which has been reported as a good source for bacteriophage isolation [13]. The TSE phages under study showed a narrow host range, a characteristic of majority of bacteriophages already reported [15].…”
Section: Resultsmentioning
confidence: 99%
“…However the development of resistant bacteria environmentally isolated Enterobacter cloacae (accession no: KF975427) strain were isolated and characterized. The TSE phages were isolated from sewage exhaust which has been reported as a good source for bacteriophage isolation [13]. The TSE phages under study showed a narrow host range, a characteristic of majority of bacteriophages already reported [15].…”
Section: Resultsmentioning
confidence: 99%
“…23 The lytic phages are likely to modulate the rate of prevalence for one or more bacteria in different microbiological niches in the body. While lytic bacteriophages against S. aureus and MRSA have been isolated from different sources such as milk, 24 sewage influent, 25 cow slurry, 26 and septic wounds, 27 it is not known if they are prevalent in the anterior nares.…”
mentioning
confidence: 99%
“…There is a wide spectrum of pathogenic bacteria that has been detected in the treated sewage and biosolids, many of which are enteric in nature (Toze 1997 (Kowal 1983;US EPA 1988;Synnott et al 2009;Dungeni et al 2010;Ellafi et al 2010;Coronel-Olivares et al 2011). Markosyan et al (2002) Salmonella spp.…”
Section: Frequently Occurred Pathogenic Bacteria In the Treated Sewagmentioning
confidence: 99%